Analisis Indeks Ketahanan Pangan di Provinsi Sumatera Selatan - Eriddunan Risvenjaya; Dedy Yuliawan; Thomas Andrian (Departement of Mathematics Education, 2024)
The agricultural sector is a very important sector in a country, because basic needs can be met by utilizing the raw products that come from this sector, if food productivity decreases, especially rice, and food consumption continues to grow, it will certainly have an impact on the emergence of a gap between food availability and needs in the midst of growing communities. This will trigger the impact of food security problems.This study aims to analyze the factors that affect food security in South Sumatra Province. The data used in this study are secondary data, while the analysis method used is the panel data regression method from 2018-2022 in South Sumatra Province. This study uses dependent variables and independent variables, the dependent variable used is food security and the independent variables include rice productivity, percentage of food expenditure and proper sanitation. The results showed that rice productivity and proper sanitation had a positive and significant effect on food security in South Sumatra Province, while the percentage of food expenditure had a negative and significant effect on food security in South Sumatra Province.